PENGARUH PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN PASIEN GAWAT DARURAT BADAN LAYANAN UMUM DAERAH RSUD BALANGAN PROVINSI KALIMANTAN SELATAN - Meiliana, Riesa; Kusbandrijo, Bambang; Rochim, Achluddin Ibnu (LPPM Institut Pendidikan Nusantara Global, 2024)
Health services are one of the many important needs for the community and are one of the basic rights of the community whose provision must be provided by the government as mandated in the 1945 Constitution Article 28 paragraph (1)